Analysis of the Relationship between Liquidity and Cost Structure to Financial Efficiency with Profitability as an Intervening Factor - Muhammad Rahmadani; Supardi Supardi; Sriyono Sriyono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the relationship between liquidity and cost structure on financial efficiency with profitability as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. Using a quantitative approach and secondary data from financial statements for the period 2019-2023, this study aims to explore the simultaneous effect of liquidity and cost structure on financial efficiency, as well as the mediating role of profitability. The results are expected to provide insights for investors and company management in making financial decisions, as well as add to the academic literature on factors that influence financial efficiency. By focusing on manufacturing companies, this study contributes to a more specific understanding of financial dynamics in the context of the industry.